Self-Disclosure and Moroccan EFL Learners' Writing Development: Effects on Complexity, Accuracy, and Fluency - Mohsine Jebbour (National Research University Higher School of Economics, 2021)
This article addressed the relationship between students' self-disclosure-that is, sharing social and positive information-and writing development in the English language classroom. The pre-test-post-test research design was adopted to assess whether students' reflections on personal positive experiences including feelings and opinions help improve their writing output as measured by complexity, accuracy, and fluency. The participants, drawn from a convenience sample, were 15 Moroccan students enrolled in the department of English studies at a Moroccan university. These participants were included to establish a homogenous level of English proficiency in writing. The participants completed a pre-test, six positive self-disclosure topics, and a post-test. A paired-sample t-test was computed to determine if a significant mean difference existed between the pre- and post-tests. Although the descriptive statistics suggest that the learners showed relative improvement in complex and fluent language, their overall writing development did not reach a statistically significant difference level. Although differing writing prompts and learners' academic learning experiences influenced the overall findings, this study contributes to the debate about the role of self-disclosure activities in improving certain language components in writing and calls for developing study programs that consider students' personal lives in language arts classes.